Pelatihan Desain Kreatif untuk Pengembangan Landing Page Website Interaktif PRM Arbuka - Septian Enggar Sukmana; Cahya Rahmad; Annisa Puspa Kirana; Moh. Zawaruddin Abdullah; Vivin Ayu Lestari; Triana Fatmawati (Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Program aimed to enhance the capacity of the board members of Pimpinan Ranting Muhammadiyah (PRM) Arbuka in managing interactive information media through creative design training for the development of a website landing page. The main problem identified was the suboptimal dissemination of organizational information to members and the surrounding community, due to the limitations of previously used social media platforms and the absence of an integrated publication medium. The training activities included understanding visual design principles, user experience (UX) design, and hands-on practice in website content creation. Evaluation results indicated that 92% of participants found the training materials to be highly relevant to the organization’s needs.